The Role of Artificial Intelligence (Ai) on Critical Thinking Skills in a Case Study of Students of the Faculty of Economics And Business (Feb) of Universitas Singaperbangsa Karawang - Pasca Arnu, Anggi; Sobandi, Ade (Perspektif Ilmu Pendidikan, 2025)
The current generation, who are living and familiar with information technology in their daily lives, including but not limited to learning purposes, Society 5.0 can also adopt artificial intelligence (AI) technology as their learning tool. Meanwhile, they face the challenge of acquiring 21st century skills that require higher order thinking (HOTS). Their reliance on the ease of AI makes students dependent, which of course has an impact on reducing students' critical thinking skills. This study was conducted to analyze the effect of AI on students' critical thinking skills. This research uses quantitative methods with research instruments in the form of questionnaires and analyzed using simple linear regression analysis. This research was conducted on students of the faculty of economics and business, University of Singaperbangsa Karawang. The research results show that AI has a positive and significant effect on students' critical thinking skills by 11.2%. Then the appropriate use of AI can be a medium to improve students' critical thinking skills